Comparison of technical and tactical parameters for elite judo athletes based on weight and gender categories - Ahmedov, F.; Gardasevic, N.; Setiawan, E.; Olimov, A.; Muqimov, O.; Jamoliddin, K.; Khuriyat, K.; Yusupov, R. (Revista Iberoamericana de Psicologia del Ejercicio y el Deporte, 2024)
Technical-tactical indicators of judo athletes play an important role in judo. The aim of this study was to compare technical-tactical indicators of combat activities of qualified judokas by weight and gender categories. National judo competitions were analyzed to collect the data and time durations of the contests, ratios of scores end by (ippon/wazari) and penalties, ratios of standing and groundwork techniques, the most dominant techniques were identified. The study results confirmed that women judo contests statistically differential from men judo fights. Also, in both genders light weigh categories fight in standing posture (nage waza), and contests end before regular time was statistically significant than heavyweight category athletes. On the other hand, uchimata, seoi nage, ouchi gari, and uchimata sukashi were among the most frequently employed techniques by judokas in both male and female categories. The results of this study can be used in the training programs to evaluate judo athletes` technical-tactical profile. In additional, the findings are can be implement creating new paradigm of training process.